Using gamified quizzes to enhance students' English reading comprehension skills - Salim, Malik; Sukarno, Sukarno; Chaudhuri, Jasim; Titania, Fani Nabila; Handayani, Riris; Haq, Ziaul; Maujud, Iswan (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2025)
This study sought to determine whether the use of quiz applications significantly impacts reading comprehension skills among students at Junior High School 1 Yogyakarta. The research employed a quasi-experimental design, utilizing pre- and post-tests administered to both control and experimental groups. The instrument of this research was a reading test that was given to 25 students in each class of pre-test and post-test. The data analyzed; the researcher used SPSS version 25. The data showed that in descriptive statistics the mean score from pretest control was 44.07 and 47.87 of pre-experiment while the test was getting more improvement in post-test. In post-control was 66.60 while post-test experiment was 80.63. In normality test showed that the significant score was >0.05 which means this test was normally distributed and homogeneity of variance showed the scores are of significance was >0.05 which meant the test was homogeneity. Finally, to analyze the impact of the quizzes in reading comprehension, the researcher used a paired sample test which showed that those pairs, namely pre-control to post control, were 0.00 which meant <0.05. Therefore, it can be concluded that there was a significantly improvement in students' reading comprehension skill in English used quizzes.